Gender incidence analysis of indirect taxes in the UK - Cristina Santos (The Open University, Economics Department, 2009)
This paper evolved from the UK research within the project on 'Gender and Taxation: Improving Revenue Generation and Social Protection in Developing Countries', a comparative international project that evaluates the impact of tax systems on gender equity in countries at various stages of their economic development.
Keywords: 330; Geschlecht; Steuerpolitik; Steuerbelastung; Indirekte Steuer; Großbritannien; Entwicklungsländer